Confirmation of TNIP1 and IL23A as susceptibility loci for psoriatic arthritis. Issue 9 (29th May 2011) - Bowes, John; Orozco, Gisela; Flynn, Edward; Ho, Pauline; Brier, Rasha; Marzo-Ortega, Helena; Coates, Laura; McManus, Ross; Ryan, Anthony W; Kane, David; Korendowych, Eleanor; McHugh, Neil; et al.
Abstract : Objectives: To investigate a shared genetic aetiology for skin involvement in psoriasis and psoriatic arthritis (PsA) by genotyping single-nucleotide polymorphisms (SNPs), reported to be associated in genome-wide association studies of psoriasis, in patients with PsA. Methods: SNPs with reported evidence for association with psoriasis were genotyped in a PsA case and control collection from the UK and Ireland. Genotype and allele frequencies were compared between PsA cases and controls using the Armitage test for trend. Results: Seven SNPs mapping to the IL1RN, TNIP1, TNFAIP3, TSC1, IL23A, SMARCA4 and RNF114 genes were successfully genotyped. The IL23A and TNIP1 genes showed convincing evidence for association (rs2066808, p = 9.1×10 −7 ; rs17728338, p = 3.5×10 −5, respectively) whilst SNPs mapping to the TNFAIP3, TSC1 and RNF114 genes showed nominal evidence for association (rs610604, p = 0.03; rs1076160, p = 0.03; rs495337, p = 0.0025). No evidence for association with IL1RN or SMARCA4 was found but the power to detect association was low. Conclusions: SNPs mapping to previously reported psoriasis loci show evidence for association to PSA, thus supporting the hypothesis that the genetic aetiology of skin involvement is the same in both PsA and psoriasis.